Evaluation of oxfendazole, praziquantel and albendazole against cystic echinococcosis: a randomized clinical trial in naturally infected sheep. - Cesar M Gavidia; Armando E Gonzalez; Eduardo A Barron; Berenice Ninaquispe; Monica Llamosas; Manuela R Verastegui; Colin Robinson; Robert H Gilman (Public Library of Science (PLoS), 2010)
Cystic Echinococosis (CE) is a zoonotic disease caused by larval stage Echinococcus granulosus. We determined the effects of high dose of Oxfendazole (OXF), combination Oxfendazole/Praziquantel (PZQ), and combination Albendazole (ABZ)/Praziquantel against CE in sheep.A randomized placebo-controlled trial was carried out on 118 randomly selected ewes. They were randomly assigned to one of the following groups: 1) placebo; 2) OXF 60 mg/Kg of body weight (BW) weekly for four weeks; 3) ABZ 30 mg/Kg BW + PZQ 40 mg/Kg BW weekly for 6 weeks, and 4) OXF 30 mg/Kg BW+ PZQ 40 mg/Kg BW biweekly for 3 administrations (6 weeks). Percent protoscolex (PSC) viability was evaluated using a 0.1% aqueous eosin vital stain for each cyst. "Noninfective" sheep were those that had no viable PSCs; "low-medium infective" were those that had 1% to 60% PSC viability; and "high infective" were those with more than 60% PSC viability. We evaluated 92 of the 118 sheep. ABZ/PZQ led the lowest PSC viability for lung cysts (12.7%), while OXF/PZQ did so for liver cysts (13.5%). The percentage of either "noninfective" or "low-medium infective" sheep was 90%, 93.8% and 88.9% for OXF, ABZ/PZQ and OXF/PZQ group as compared to 50% "noninfective" or "low-medium infective" for placebo. After performing all necropsies, CE prevalence in the flock of sheep was 95.7% (88/92) with a total number of 1094 cysts (12.4 cysts/animal). On average, the two-drug-combination groups resulted pulmonary cysts that were 6 mm smaller and hepatic cysts that were 4.2 mm smaller than placebo (p<0.05).We demonstrate that Oxfendazole at 60 mg, combination Oxfendazole/Praziquantel and combination Albendazole/Praziquantel are successful schemas that can be added to control measures in animals and merits further study for the treatment of animal CE. Further investigations on different schedules of monotherapy or combined chemotherapy are needed, as well as studies to evaluate the safety and efficacy of Oxfendazole in humans.